Progressive Tumefactive Demyelination as the Only Result of Extensive Diagnostic Work-Up: A Case Report - Štourač, Pavel; Kolčava, Jan; Keřkovský, Miloš; Kopřivová, Tereza; Křen, Leoš; Bednařík, Josef (Frontiers in Neurology, 2021)
Tumefactive demyelinating lesions belong to the rare variants of multiple sclerosis, posing a diagnostic challenge since it is difficult to distinguish them from a neoplasm or other brain lesions and require a careful differential diagnosis. This contribution presents the case report of a young female with progressive tumefactive demyelinating brain and spinal cord lesions. An extensive diagnostic process including two brain biopsies and autopsy did not reveal any other explanatory diagnosis other than multiple sclerosis. The patient was treated by various disease-modifying treatments without significant effect and died from ascendent infection via ventriculoperitoneal shunt resulting in Staphylococcus aureus meningitis.